PELAKSANAAN PEMBERIAN LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH DASAR NEGERI 200111 PADANG SIDEMPUAN OLEH GURU KELAS - Monica Theresia; Neviyarni Neviyarni (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
This study aims to determine the implementation of the provision of guidance and counseling services by classroom teachers and find out how the development and change of students in the State Elementary School 200111 Padangsidimpuan after receiving guidance and counseling services from class teachers. This research is a qualitative research with a descriptive model. The sample of this study was 12 classroom teacher respondents in 200111 Padangsidimpuan Public Elementary School. The way to collect data is by interview and documentation. The method of data analysis in research is by data reduction, data presentation, drawing conclusions and verification. Researchers obtained information that the implementation of guidance and counseling services performed by class teachers includes in four parts of guidance and counseling. The four sections are in the areas of personal, social, study and career guidance. The provision of guidance and counseling services according to their fields is carried out by providing enthusiasm, advice and motivation to students. This study concludes the implementation of guidance and counseling services carried out by each class teacher using electic counseling techniques and the results of the guidance obtained is that there are changes in attitudes and abilities shown by students in a direction that is better than before. Keywords: Implementation of Guidance and Counseling Services, Class Teachers, Elementary Schools